PERANCANGAN ALUR PENGIRIMAN MENGGUNAKAN SHIPPING OPERATION DIAGRAM DI PT VELASTO (STUDI KASUS PADA PT NAMICOH) - Hendi Iskandar; Asep Andrian Rahmat Saputra; Raihan Hamdhan Zulva (STKIP Pesisir Selatan, 2026)
Objective: This study aims to analyze and design the shipping flow using the Shipping Operation Diagram (SOD) method at PT Velasto Indonesia for shipments to PT Namicoh Indonesia. The main problems include delivery delays, inconsistent processing times, and a lack of workflow visualization, which impacts coordination between departments.The methods used were observation, interviews, documentation, and 5W+1H analysis. The results indicate that delays are caused by inconsistencies in product availability, not good (NG) status, and differences in stock data. The preparation phase is the most critical activity due to its time consumption and instability.The implementation of SOD clarifies the workflow and establishes time standards for each activity. As a result, time efficiency increased by 14.29% (from 105 minutes to 90 minutes), and the shipping process became more structured and consistent.